If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(3x + 2) = -3(2x + -4) + -4x Reorder the terms: 5(2 + 3x) = -3(2x + -4) + -4x (2 * 5 + 3x * 5) = -3(2x + -4) + -4x (10 + 15x) = -3(2x + -4) + -4x Reorder the terms: 10 + 15x = -3(-4 + 2x) + -4x 10 + 15x = (-4 * -3 + 2x * -3) + -4x 10 + 15x = (12 + -6x) + -4x Combine like terms: -6x + -4x = -10x 10 + 15x = 12 + -10x Solving 10 + 15x = 12 + -10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10x' to each side of the equation. 10 + 15x + 10x = 12 + -10x + 10x Combine like terms: 15x + 10x = 25x 10 + 25x = 12 + -10x + 10x Combine like terms: -10x + 10x = 0 10 + 25x = 12 + 0 10 + 25x = 12 Add '-10' to each side of the equation. 10 + -10 + 25x = 12 + -10 Combine like terms: 10 + -10 = 0 0 + 25x = 12 + -10 25x = 12 + -10 Combine like terms: 12 + -10 = 2 25x = 2 Divide each side by '25'. x = 0.08 Simplifying x = 0.08
| 174=121-w | | 31=-4x-5x-5 | | 2e^4x+7=107 | | 182=42-y | | 9u+4u=30 | | 747+(-60)=0 | | 1/8x−49/8 | | 188=29-x | | 6(3x-3)(x-4)=0 | | 43-y=174 | | 6g+27=36 | | y+63=8y | | (x-7)(-1)=0 | | .08=.03+.60*.05 | | 10y=21+7y | | .08=.03+.03 | | 3x+5=2(2x-1)1-(x-3) | | -3/5c-7=6 | | 227=142-u | | 18m+9=3(4m-9) | | (x-7)(4)=0 | | 23-x=275 | | -0.6c-7=6 | | 3-5x-7x=87 | | 14x-3=9x+5 | | 168=19-v | | 2+e=-2 | | ln(5x)+ln(10x)= | | 3(5x+3)=-5(5x-2) | | v+60=5v | | 3x+90=126 | | 6x=9y-6 |